1988
DOI: 10.1164/ajrccm/137.6.1371
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Lung Water Distribution by Nuclear Magnetic Resonance: A New Method for Quantifying and Monitoring Experimental Lung Injury

Abstract: We have developed a new analytical method that uses nuclear magnetic resonance (NMR) imaging data to quantify lung water content and distribution. This new method generates a distribution of lung water density in which the fraction of voxels corresponding to a given water density is plotted on the vertical axis as a function of water density on the horizontal axis, thereby complementing the spatial information provided by the NMR image. We obtained reproducible lung water distribution data at comparable lung v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Repeated measures of lung water by NMR vary by about 5-10% [20]. Numerous studies have reported a good correlation between NMR-determined estimates of lung water and estimates from the gold-standard gravimetric method [21,22,23,24,25,26].…”
Section: Imaging Methodsmentioning
confidence: 99%
“…Repeated measures of lung water by NMR vary by about 5-10% [20]. Numerous studies have reported a good correlation between NMR-determined estimates of lung water and estimates from the gold-standard gravimetric method [21,22,23,24,25,26].…”
Section: Imaging Methodsmentioning
confidence: 99%
“…Also, abnormalities in lung hypoxia have been described in vivo in the isolated pigs lung [6]. Studies of lung edema with MRS have also proven useful [7]. Two methods of lung injury in the rat were chosen for study.…”
Section: Discussionmentioning
confidence: 99%
“…1 B). not monoexponential (13). Whole lung and regional pHzO values are therefore reported only to document their variability among lung regions or their changes associated with pulmonary edema.…”
Section: Discussionmentioning
confidence: 99%
“…NMR lung water content was measured in a coronal (frontal) lung section midway between the anterior and posterior chest wall, which in previous studies has been found to be adequately representative of the whole lung (13). The right and left lungs were outlined using a cursor (the mediastinal structures were excluded).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation